Literasi Musik Tari Pada Personil Sanggar Seni Sekintang Dayo Sungai Kambang Kota Jambi - syahrial (UPT Perpustakaan Universitas Jambi, 2024)
This research discusses the personnel of Sekintang Dayo art studio. The purpose of this study is to know how the ability of the problem in accessing, evaluating and how to use and communicate information about dance music. This research is qualitative research with descriptive approach and data collection through interview method, observation and documentation. Based on the analysis and research findings, the ability of the artist members Sekintang Dayo art to access information can be categorized well. This can be seen from 18 informants who identify the sources of information used through Youtube, Instagram, Facebook, and TV, as a medium of information access. Then The ability of personnel in evaluating information can be categorized well. It can be seen that personnel evaluate the music information they obtain by comparing and sorting information. The personnel's ability to use and disseminate information can be categorized well. It can be seen that they have their own application account to disseminate music information dance.